Penggunaan Antibiotik dan Resistensi Escherichia coli and Klebsiella pneumoniae: Studi Ekologikal Lima Tahun di Sebuah Rumah Sakit Umum Daerah - Sanjaya, Dwi Arymbhi; Meriyani, Herleeyana; Juanita, Rr. Asih; Siada, Nyoman Budiartha; Mahaputra, Yudistira; Kamalia, Made Gek Adisti (Jurnal Ilmiah Medicamento, 2025)
Antibiotic resistance is a growing global health threat, partly driven by high antibiotic consumption. The World Health Organization (WHO) has identified critical-priority bacteria, including Escherichia coli and Klebsiella pneumoniae, due to their increasing resistance to multiple antibiotics. This study aimed to evaluate the correlation between antibiotic consumption and resistance rates in Escherichia coli and Klebsiella pneumoniae. This ecological study was conducted at a Regional Hospital in Indonesia based on retrospective inpatient data from January 2019 to December 2023. The population in this study is all data on systemic antibiotic consumption based on the J01 category of the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) classification system and antibiogram from inpatient databases. Pearson and Spearman’s rank correlation analyses were performed to examine the associations between systemic antibiotic consumption levels and the percentage of Escherichia coli and Klebsiella pneumoniae resistance to other antibiotics. The most frequently used antibiotics were cefixime (305.664 DDD/100 bed-days), levofloxacin (139.552 DDD/100 bed-days), and ceftriaxone (109.805 DDD/100 bed-days). A strong and statistically significant correlation was observed between doxycycline consumption and Escherichia coli resistance to meropenem (r=0.894; p=0.041). Moreover, consumption levels of cefazolin, ceftazidime, cefepime, and ciprofloxacin were correlated with Escherichia coli resistance to ceftriaxone (p<0.05), while cefoperazone use demonstrated a very strong and statistically significant correlation with Escherichia coli resistance to ampicillin-sulbactam (r=0.952; p=0.012). Conversely, no significant correlation was found between antibiotic consumption and resistance in Klebsiella pneumoniae, suggesting that alternative factors such as intrinsic resistance mechanisms, mobile genetic elements, and environmental reservoirs may influence resistance development.